1996
DOI: 10.1007/s002560050130
|View full text |Cite
|
Sign up to set email alerts
|

Spinal osteoblastoma: relationship between paravertebral muscle abnormalities and scoliosis

Abstract: Nine patients had scoliosis. All patients with a thoracic or lumbar lesion and scoliosis (n = 8) had an associated abnormality of the paravertebral muscles (usually atrophy with fatty replacement). One patient with a lumbar lesion and no scoliosis had normal paravertebral muscles. One patient with a cervical lesion had thoracic scoliosis but no muscle abnormality in the cervical region, while two patients with cervical lesions and no scoliosis showed muscle abnormalities. The results support the clinical hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Unlike Type A, these lesions infiltrated the skeletal musculature, rather than being localized to the peri-vertebral connective tissues and associated septa, which has been previously observed in severely affected fish (Munday et al, 2016). This is consistent with Type B MRI signals representing a more advanced stage of the reparative process than Type A, as mature fibrosis is considered a 'hallmark' of chronic inflammatory response processes (Munday et al, 2016;Saifuddin et al, 1996).…”
Section: Histopathologysupporting
confidence: 83%
See 1 more Smart Citation
“…Unlike Type A, these lesions infiltrated the skeletal musculature, rather than being localized to the peri-vertebral connective tissues and associated septa, which has been previously observed in severely affected fish (Munday et al, 2016). This is consistent with Type B MRI signals representing a more advanced stage of the reparative process than Type A, as mature fibrosis is considered a 'hallmark' of chronic inflammatory response processes (Munday et al, 2016;Saifuddin et al, 1996).…”
Section: Histopathologysupporting
confidence: 83%
“…In humans with scoliosis, the paravertebral muscle on the concave side of the curvature shortens, stiffens, and atrophies, but lengthens and hypertrophies on the convex side (Kim et al., 2013; Saifuddin et al., 1996). This may explain why Type A signal was consistently on the concave side of scoliotic, but not lordotic or kyphotic, curvatures.…”
Section: Discussionmentioning
confidence: 99%
“…51 In addition, in cases where scoliosis has developed, the paraspinal muscles along the concave aspect of the curvature demonstrate various degrees of atrophy. 52 Secondary aneurysmal bone cysts with fluid-fluid levels may arise in 10% of osteoblastomas. 44 Periosteal osteoblastomas have a different appearance than the much more common intramedullary osteoblastomas.…”
Section: Osteoblastomamentioning
confidence: 99%
“…Ozaki et al reported scoliosis in 77% (17/22) of their patients, with an improvement seen in 16 of the 17 after tumor resection [15]. The tumors are found on the concavity of the scoliosis with a proposed etiology being muscle spasms secondary to inflammatory factors [18].…”
Section: Discussionmentioning
confidence: 99%